ANALISIS PENDAPATAN USAHATANI CABAI MERAH DI DESA NOELBAKI KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Zelestika, Anastasia; Un, Paulus; Bano, Maria (Buletin Ilmiah Impas, 2024)
This study aims to determine the amount of red chili farmers' income in Noelbaki Village,Kupang Tengah District,Kupang Regency,and to determine the feasibility of red chili farming in Noelbaki Village,Kupang Tengah District, Kupang Regency. The population in this study were farmers who cultivate red chili plants as many as 92 farmers.While the determination of the sample was carried out by simple random sampling so that 31 people were obtained.The results showed that: (1). The total cost incurred for red chili farming is Rp.177,768,807/ha with a total revenue of IDR 908,000,000/ha and income of IDR 730,231,193/year/ha.(2).The feasibility R/C ratio of red chili farming in the study area in Noelbaki Village, Kupang Tengah District, Kupang Regency is 5.10 where the R/C ratio is > 1, which means that red chili farming in the study area is feasible or profitable